PROFITABILITAS, RASIO SOLVABILITAS DAN HARGA SAHAM; STUDI EMPIRIK PADA PERUSAHAAN SUBSEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Akhmadi Akhmadi; Andhika Ragil Prasetyo (Jurnal Riset Akuntansi Terpadu, 2018)
The purpose of this study is to analyze and interpret the influence on prices sahama Profitability in the coal subsector listed in Indonesia Stock Exchange 2010-2014. This type of research is the study of associative (causal). Populasi used in this study is a coal mining company listed on the Stock Exchange Period 2010-2014 as many as 23 companies. The method used to determine the sample using purposive sampling, so that the resulting sample was observed to 11 companies. The data used is secondary data. Analysis of data using multiple linear regression analysis. Research to produce empirical evidence that the profitability of significant positive effect on stock prices. While solvency is not significant positive effect on stock prices.